Teacher Leadership Development in Elementary Schools in South Minahasa Regency - Tombokan, Sarah S.N; Lengkong, Jeffry Sony Junus; Maru, Mister Gideon; Tambingon, Henny Nikolin (International Journal of Information Technology and Education, 2026)
The development of teachers’ roles extends beyond teaching to leadership roles. This study aims to describe and identify teacher leadership development, its determinants, and its outcomes in elementary school settings. This study employed a case study method with a multi-case study design. The primary data source was an informal group of 11 participants, consisting of three principals and eight teachers. Data collected through interviews, observations, and documentation studies were processed using qualitative data analysis techniques using an interaction model. The validity of the research data was tested using credibility, transferability, dependability, and confirmability techniques. The results of the study are presented in three findings. First, elementary school teacher leadership development occurs through teacher learning, the boundaries of teacher leadership encompassing the classroom, group, and organization, and roles within and outside the school. Second, the determinants of elementary school teacher leadership development include internal and external factors, as well as interactions between principals and teachers. Third, the results of elementary school teacher leadership development include outcomes at the teacher, student, and school levels. The results of this study are discussed in relation to theory and empirical evidence from previous research. Furthermore, the research conclusions and recommendations are described